Interatomic potential for Fe–Cr–Ni–N system based on the second nearest-neighbor modified embedded-atom method. Issue 15 (12th October 2016) - Tong, Ke; Ye, Fei; Gao, Muziyuan; Lei, Ming Kai; Zhang, Chi
Abstract: The interatomic potential for Fe–Cr–Ni–N system based on the second nearest-neighbour modified embedded-atom method has been developed in this work. The potential is based on those for the corresponding lower order systems. The potential parameters for the binary systems, Cr–N, Ni–N, Ni–Fe and Ni–Cr, were determined by fitting the lattice constants, elastic properties, heat of solution and defect binding energies. The potential parameters for the ternary systems were calculated based on the corresponding binary systems. Then, all of them were applied to the quaternary system Fe–Cr–Ni–N to confirm their validity by a simulation of the lattice constants of AISI 316 austenitic stainless steel with a range of nitrogen content. The results were in good agreement with the previous observations and calculations.